The Effect Of Anaerobic Physical Exertion According To The Variance Of The Gene (MCT1) On The Level Of Lactic Acid Concentration In The Blood And The Achievement Of 200 M Free Swimming - Sabah Mohammed Al-Khafaji, Wafaa; Ibrahim Suhail Al-Kinani, Suadad; Aamer Ali Al Azawi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the heterogeneity of the MCT1 gene in the 200-meter freestyle swimmer and its effect on the level of lactic acid concentration in the blood and the completion of the 200-meter freestyle swim. Free according to the heterogeneity of the MCT1 gene. The sample of the research was chosen by the intentional method with the middle Euphrates swimmers participating in the Iraqi men’s swimming championship for the 2017-2018 sports season, free-swimming, as they numbered 12 swimmers. Measuring the MCT1 gene at rest) (measuring the concentration of lactic acid in the blood during rest and after 5 minutes of effort) (achievement of the 200-meter free-swimming race). The researcher concluded that the difference in the heterogeneity of the MCT1 gene for the research sample of swimmers was within two levels, high and low, and that the level of lactic acid concentration in the blood after anaerobic physical exertion for the 200m freestyle race was less high for the group with the high level of the MCT1 gene compared to the low group, and this confirms that individuals who have The heterogeneity of the MCT1 gene is high, their ability to endurance and resistance to fatigue is greater, and the completion time for the 200-meter freestyle race was less time for individuals with a high level of the MCT1 gene compared to individuals with a low level, and this confirms that individuals who have a high rate of variation of the MCT1 gene have a level of physical efficiency high and achieve better